ナンキョク ミナミ ビクトリアランド ノ ドライバレー チイキ ニ オケル エンコ ノ ストロンチウム - 三好, 登和子; ミヨシ, トワコ; 今橋, 正征; イマハシ, マサユキ; 鳥居, 鉄也; トリイ, テツヤ; Miyoshi, Towako; Imahashi, Masayuki; Torii, Tetsuya (1988)
P(論文) 南Victoria LandのDry Valley地域には多くの塩湖が点在する。それら塩湖水中のストロンチウム濃度を測定したところ, 0.0-1630mg/lであった。そこでそれらのSr/Ca比を求めたところ, 0.0-4.56×(10)^<-2>の範囲で, 内陸の塩湖水のSr/Ca比はRoss海に近い塩湖水の比よりも低いことが明らかになった。Dry Valley地域の塩湖の塩起源をSr/Ca比をもとに, 次のように要約した。1)Fryxell湖の塩類は海水に起因する。すなわち, 湖水のSr/Ca比, 約3-4×(10)^<-2>, はhaliteが蒸発析出した海水の比に似た値である。現在の塩水は, 塩分が1/5ほどであるので, 蒸発した海水と氷河融水との混合により形成したと思われる。Bonney湖の塩類もまたFryxell湖と同じような変化を経て生成したと考えられる。2)Vanda湖は, 岩石風化で生じた塩類や海水起源の塩類析出物を含んでいる氷河融水と, Onyx河川水で形成された。谷中に分布するcalciteやgypsumのような塩類析出物は, T. G. THOMPSONとK. H. NELSON (Am. J. Sci., 254,227,1956)により行われた低温下での凍結濃縮で海水から生成されたと思われる。3)Wright谷上流域のLabyrinth地帯の湖沼水は, 氷河融水や降雪による風送塩の溶解や, 玄武岩といくぶん反応した水から生じたと考えられる。 The Sr concentrations of saline lake waters collected from the Dry Valleys region of Victoria Land were determined and the Sr/Ca ratios were evaluated. These waters have various Sr/Ca ratios ranging from 0.0 to 4.56×(10)^<-2>. It was observed that the Sr/Ca ratios of inland lake waters were smaller than those of the lakes near the Ross Sea. On the basis of the Sr/Ca ratios the origin of lake waters in the Dry Valleys region is summarized as follows : 1) The water in Lake Fryxell was originated from evaporated seawater under frigid conditions, because the Sr/Ca ratio of the water, about 3 to 4×(10)^<-2>, is similar to that of evaporated seawater from which halite is deposited. This water may have been formed by mixing of the evaporated seawater with glacial meltwater. It is likely that the water in Lake Bonney was also formed in a similar manner to that of Lake Fryxell. 2) The water in Lake Vanda was originated from glacial meltwater containing dissolved marine evaporites. The evaporites such as calcite and gypsum in the valley may have been formed under frigid conditions as delineated by T. G. THOMPSON and K. H. NELSON (Am. J. Sci., 254,227,1956). 3) The water in the Labyrinth area was probably originated from the dissolution of air-borne salts by glacial meltwater and snowfall and the waters drived from fresh water-basalt interactions. ...